2022
DOI: 10.1097/corr.0000000000002111
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Maximum Tibial Tunnel Angle for Transtibial PCL Reconstruction? A Comparison Based on Virtual Radiographs, CT Images, and 3D Knee Models

Abstract: Background To minimize the killer turn caused by the sharp margin of the tibial tunnel exit in transtibial PCL reconstruction, surgeons tend to maximize the angle of the tibial tunnel in relation to the tibial plateau. However, to date, no consensus has been reached regarding the maximum angle for the PCL tibial tunnel. Questions/purposes In this study we sought (1) to determine the maximum tibial tunnel angle for the anteromedial and anterolateral approaches in transtibial PCL reconstruction; (2) to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…With respect to sex, there was no significant difference in the mean value of the PSA, but there were significant differences in the TTH and TTD between male and female (Table 1). With respect to age, the included patients were divided into a young group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), a middle-aged group (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) and an elderly group (46-60) (Table 2). The outcome parameters showed that the mean value of PSA of T4 in the middle-age group was significantly lower than that in the young (P = 0.026), Both the TTH and TTD (T4 and T5) of the middle-age and the elderly groups were significantly higher than that of the young group (P < 0.05).…”
Section: Subgroup Analysis In Terms Of Sex Age and Heightmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to sex, there was no significant difference in the mean value of the PSA, but there were significant differences in the TTH and TTD between male and female (Table 1). With respect to age, the included patients were divided into a young group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), a middle-aged group (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) and an elderly group (46-60) (Table 2). The outcome parameters showed that the mean value of PSA of T4 in the middle-age group was significantly lower than that in the young (P = 0.026), Both the TTH and TTD (T4 and T5) of the middle-age and the elderly groups were significantly higher than that of the young group (P < 0.05).…”
Section: Subgroup Analysis In Terms Of Sex Age and Heightmentioning
confidence: 99%
“…The 3D knee model simulation is a novel method which could provide an in-vitro virtual technique to simulate the tibial tunnel. 25 Previous studies have reported, the 3D knee model could be used in precise quantitative analysis and has excellent measurement accuracy and reliability. 26 Based on the 3D knee model, the tibial tunnel could be monitored in real time, and the PSAs in different tibial tunnel approaches could be accurately measured and analyzed in 3D space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported that this angle could not be increased excessively, for the tibial posterior wall may break and cause risk to the neurovascular bundles in the posterior popliteal fossa. 3,[21][22][23] Recently, Teng et al 10 have reported that the maximum tibial tunnel angle (ATP) for the anteromedial approach in transtibial PCL reconstruction is 58 .…”
Section: Anterolateral Approach Compared To Anteromedial Approachmentioning
confidence: 99%
“…Although previous studies have used cadaveric and biomechanical models to evaluate the killer turn angle, few studies quantitively analyzed this angle 7 . Due to the limitations of the cadaveric and biomechanical models, the effect of the varied tibial tunnel approach on the 3D killer turn angle is often not accurately analyzed 10 . Fortunately, a novel method of the 3D knee model establishes an in‐vitro virtual simulation technique, which provides great advantages in precise quantitative analysis and credible repeatability 11–13 .…”
Section: Introductionmentioning
confidence: 99%